2023
DOI: 10.1039/d2nr05381k
|View full text |Cite
|
Sign up to set email alerts
|

Cauliflower-like NiFe alloys anchored on a flake iron nickel carbonate hydroxide heterostructure towards superior overall water and urea electrolysis

Abstract: Exploring efficient, stable and multifunction earth-rich electrocatalysts is vital for hydrogen generation. Hence, an efficient heterostructure consisting of cauliflower-like NiFe alloys anchored on flake iron nickel carbonate hydroxide which supported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…29 Binary metals and their alloying effect may change the adsorption energy of the intermediate products and adjust the position of the d-band center to improve the intrinsic activity of the catalysts. 30 Studies have shown that surface modified or functionalized Ni substrates with various defects through physical and chemical approaches exhibit enhanced electron transfer kinetics, without having surface poisoning, augmenting the oxygen/urea oxidation reaction. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…29 Binary metals and their alloying effect may change the adsorption energy of the intermediate products and adjust the position of the d-band center to improve the intrinsic activity of the catalysts. 30 Studies have shown that surface modified or functionalized Ni substrates with various defects through physical and chemical approaches exhibit enhanced electron transfer kinetics, without having surface poisoning, augmenting the oxygen/urea oxidation reaction. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…56 Also, transition metal alloys can improve the electronic structure of the catalyst surface and enhance the catalytic activity and stability. 57 In addition, carbon materials are widely used as important compositions to improve the conductivity of the electrocatalysts in a variety of electrochemical conversion devices. Among various carbon-based materials, carbon nanobers (CNFs) have generated great interest in eminent research due to their intrinsic advantages such as lightweight, high electrical conductivity, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…56 Also, transition metal alloys can improve the electronic structure of the catalyst surface and enhance the catalytic activity and stability. 57 However, most catalysts were limited by single functionality or low activity, therefore, it is expected to construct multifunctional catalysts with high activities by composite multiple components.…”
Section: Introductionmentioning
confidence: 99%